2020
DOI: 10.14785/lymphosign-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effects of systemic lupus erythematosus: the imitator of aging

Abstract: Objectives: To assess the psychological effects of systemic lupus erythematosus (SLE), including perception of aging, in a cohort of participants who were either diagnosed with SLE or had an affected family member. Methods: Over a period of 1 year, we conducted once-monthly face-to-face interviews with 12 participants. The participants were from 4 related families and include 7 females and 5 males. Three participants had a confirmed diagnosis of SLE. Spouses were also included in this study to assess transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Interestingly, the reduction shown in this study in SLE self-reported symptoms was associated with an improvement in mental health outcomes (Quality of Life, SLE-related shame and pain cognitions). We believe that this further supports the mind-body connection in SLE, which has already been established in both quantitative [ 46 ] and qualitative [ 47 ] studies. Thus, when one’s physical symptoms improve, so too do aspects of psychological distress, and vice versa.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the reduction shown in this study in SLE self-reported symptoms was associated with an improvement in mental health outcomes (Quality of Life, SLE-related shame and pain cognitions). We believe that this further supports the mind-body connection in SLE, which has already been established in both quantitative [ 46 ] and qualitative [ 47 ] studies. Thus, when one’s physical symptoms improve, so too do aspects of psychological distress, and vice versa.…”
Section: Discussionsupporting
confidence: 86%
“…In a study on this subject, it was revealed that SLE causes psychological signs of aging [11]. According to another study, the effect of menstruation on the perception of aging through the imitation of menopause was proven [9].…”
Section: Introductionmentioning
confidence: 94%
“…The mirror neuron system, which people activate for adaptation to the environment, facilitates learning about other living things thanks to its imitation ability [8]. Behaviors are simulated by observing the movements of living things through imitation [9][10][11]. Diseases that Systemic Lupus Erythematosus (SLE) patients observed are imitated.…”
Section: Introductionmentioning
confidence: 99%